2017
DOI: 10.1038/srep43920
|View full text |Cite
|
Sign up to set email alerts
|

A peptide vaccine targeting angiotensin II attenuates the cardiac dysfunction induced by myocardial infarction

Abstract: A peptide vaccine targeting angiotensin II (Ang II) was recently developed as a novel treatment for hypertension to resolve the problem of noncompliance with pharmacotherapy. Ang II plays a crucial role in the pathogenesis of cardiac remodeling after myocardial infarction (MI), which causes heart failure. In the present study, we examined whether the Ang II vaccine is effective in preventing heart failure. The injection of the Ang II vaccine in a rat model of MI attenuated cardiac dysfunction in association wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Mixtures of synthetic peptides derived from cat allergen epitopes have been successfully used to induce tolerance in clinical phase 2 tests ( 62 ). A peptide vaccine targeting angiotensin II was recently developed as a novel treatment for hypertension and the prevention of heart failure ( 63 ). Applications of immunodominant-epitope-based cancer vaccines combined with other strategies have significantly enhanced the specificity and safety of T-cell responses targeting to tumors ( 64 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mixtures of synthetic peptides derived from cat allergen epitopes have been successfully used to induce tolerance in clinical phase 2 tests ( 62 ). A peptide vaccine targeting angiotensin II was recently developed as a novel treatment for hypertension and the prevention of heart failure ( 63 ). Applications of immunodominant-epitope-based cancer vaccines combined with other strategies have significantly enhanced the specificity and safety of T-cell responses targeting to tumors ( 64 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…These effects of Ang II are correlated with the pathophysiology of MI. MI induces morphological changes called remodeling, which leads to heart failure accompanied by infarct area extension and thinning and compensatory hypertrophy of the non-infarcted myocardium [ 37 ]. Ang II-induced reactions may further damage the myocardium and accelerate post-MI remodeling [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study concluded that the Ang II-KLH vaccine diminished the cardiac remodeling that results in heart failure, improving cardiac function and suppressing adverse pathological changes in a rat model of myocardial infarction. In regard to the safety of the Ang II-KLH vaccine, no visible pathological changes were observed in various organs (heart, lung, liver, spleen, and kidney) and did not affect the levels of serum cystatin C, plasma brain natriuretic peptide-45, and serum albumin which reflect renal, cardiac, and hepatic function, respectively [27].…”
Section: Angiotensin IImentioning
confidence: 94%